The Saint of Fort Washington - Hunter, Tim (Viva Video, 2003)
Matthew is a young white guy kicked out onto the street after years of institutional care. Jerry is a black Vietnam veteran who has lost his wife, family and home to the man who was once his best friend. They forge a friendship so deep that no amount of suffering can destroy it. Their ambition is modest: all they want is enough money to build a new life and recover their dignity. They want to start a business, running a fruit truck in New Jersey. On the Streets of New York they make a living the only way they can - cleaning windshields. A mixture of acid one liners and ridiculous praise usually makes the drivers give them something - but it takes talent... and Matthew discovers he has it. A moving story of love and courage, when the odds are stacked a mile high against survival, will crack the hardest heart and enthrall the audience.